Differential gene expression by Paracoccidioides brasiliensis in host interaction conditions: Representational difference analysis identifies candidate genes associated with fungal pathogenesis - Bailao, Alexandre Melo; Schrank, Augusto; Borges, Clayton Luiz; Dutra, Valeria; Walquiria Ines Molinari-Madlum, Eugenia Emilia; Soares Felipe, Maria Sueli; Mendes-Giannini, Maria José Soares [UNESP]; Martins, Wellington Santos; Pereira, Maristela; de Almeida Soares, Celia Maria (Elsevier B.V., 2006)
Paracoccidioides brasiliensis causes infection by the host inhalation of airborne propagules of the mycelia phase of the fungus. These particles reach the lungs, and disseminate to virtually all organs. Here we describe the identification of differentially expressed genes in studies of host-fungus interaction. We analyzed two cDNA populations of P. brasiliensis, one obtained from infected animals and the other an admixture of fungus and human blood thus mimicking the hematologic events of the fungal dissemination. Our analysis identified transcripts differentially expressed. Genes related to iron acquisition, melanin synthesis and cell defense were specially upregulated in the mouse model of infection. The upregulated transcripts of yeast cells during incubation with human blood were those predominantly related to cell wall remodeling/synthesis. The expression pattern of genes was independently confirmed in host conditions, revealing their potential role in the infection process. This work can facilitate functional studies of novel regulated genes that may be important for the survival and growth strategies of P. brasiliensis in humans. (c) 2006 Elsevier Masson SAS. All rights reserved.
Keywords: Paracoccidioides brasiliensis; representational difference analysis; infection